2000
DOI: 10.1111/j.1651-2227.2000.tb00087.x
|View full text |Cite
|
Sign up to set email alerts
|

Cost analysis of the treatment of acute childhood lymphocytic leukaemia according to Nordic protocols

Abstract: Some attempts have been made to reduce the costs incurred in the therapy of leukaemia, but no studies are available regarding costs of the entire treatment in children with acute lymphocytic leukaemia (ALL). We analysed all the direct costs of treatment of 11 children with ALL diagnosed and treated in Kuopio University Hospital. The follow-up continued from diagnosis until the end of treatment for each patient. Patient treatment on the ward lasted for 84-210 d and in the outpatient clinic for 24-66 d, dependin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
25
0

Year Published

2000
2000
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(27 citation statements)
references
References 21 publications
2
25
0
Order By: Relevance
“…This variation was due to; the age and size of the patient which determined drug dosage, supportive care needs, the cost of episodes of infection and food, lodging and travel costs. This cost was considerably lower than the costs reported from high income countries even if one was to take into account purchasing power parity corrections [4]. Even so the cost to poor families is still prohibitively high.…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…This variation was due to; the age and size of the patient which determined drug dosage, supportive care needs, the cost of episodes of infection and food, lodging and travel costs. This cost was considerably lower than the costs reported from high income countries even if one was to take into account purchasing power parity corrections [4]. Even so the cost to poor families is still prohibitively high.…”
Section: Discussionmentioning
confidence: 92%
“…In contrast using a Nordic protocol conducted at the Department of Pediatrics in Kuopio University Hospital, Finland. Rahiala et al [4] reported that the average cost of treatment for their 11 patients was 100,000 USD.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The most common form of childhood cancer is leukaemia, and although true estimates of financial cost have been made before, the paper recently published in Acta Paediatrica by Raihala and colleagues (2) gives us a detailed breakdown of how much it really costs to treat children on the Nordic protocols. By costing each and every facet of treatment they have come up with a total cost of USD 103,250 per child.…”
mentioning
confidence: 98%
“…6 The blood products account for 4% of the total costs of ALL treatment per patient. 7 Safety requirements such as leukocyte depletion and irradiation increase the cost and complexity of transfusions.…”
mentioning
confidence: 99%